2017
DOI: 10.1017/age.2017.21
|View full text |Cite
|
Sign up to set email alerts
|

Consumer Preferences for Oyster Attributes: Field Experiments on Brand, Locality, and Growing Method

Abstract: Oyster aquaculture has experienced tremendous growth in the United States over the past decade, but little is known about consumer preferences for oysters. This study analyzed preferences for oysters with varied combinations of brands, production locations, and production methods (aquaculture vs. wild-caught) using dichotomous choice, revealed preference economic field experiments. Results suggest significant and distinct differences in behavior between first-time and regular oyster consumers. While infrequent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 18 publications
1
22
0
Order By: Relevance
“…16 Since there is economic benefit in keeping seafood alive, shellfish may need to be kept in saltwater environments; however, few studies have examined plasma directly applied to seawater. 17,18 For example, a study showed that PAW containing 0.9% wt/vol NaCl effectively reduced planktonic Listeria monocytogenes and E. coli O157:H7. 19 Another study mixed PAW with simulated seawater (SS) to reduce Vibrio alginolyticus, Vibrio harveyi, Vibrio parahaemolyticus, and Edwardsiella tarda attachment on the cysts of Artemia salina.…”
Section: Introductionmentioning
confidence: 99%
“…16 Since there is economic benefit in keeping seafood alive, shellfish may need to be kept in saltwater environments; however, few studies have examined plasma directly applied to seawater. 17,18 For example, a study showed that PAW containing 0.9% wt/vol NaCl effectively reduced planktonic Listeria monocytogenes and E. coli O157:H7. 19 Another study mixed PAW with simulated seawater (SS) to reduce Vibrio alginolyticus, Vibrio harveyi, Vibrio parahaemolyticus, and Edwardsiella tarda attachment on the cysts of Artemia salina.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, researchers have investigated consumer valuations for a variety of oyster attributes (Alfnes, Chen, & Rickertsen, 2018;Li & Messer, 2019). Examples include the nutrient level of the watershed from which they are harvested (Li, Kecinski, & Messer, 2018), growing methods (Kecinski, Messer, Knapp, & Shirazi, 2017), concerns about human health associated with eating raw oysters (Petrolia, Walton, & Acquah, 2014), product packaging (Loose, Peschel, & Grebitus, 2013), and type of harvest location such as wild-caught versus aquaculture (Chen, Haws, Fong, & Leung, 2017). Generally, these studies have found that consumers are sensitive to the harvest location of oysters and are willing to pay a premium for locally produced oysters (see Chen et al (2017) for a choice experiment conducted in Hawaii, and Li, Kecinski, and Messer (2017) for a field experiment conducted in the U.S. East Coast).…”
Section: Introductionmentioning
confidence: 99%
“…The main challenges with these intervention strategies are the regulations governing their implementation, validation, and verification of implemented intervention as well as access to the facility. In addition, the wide‐scale commercial application of these intervention strategies may be challenged by consumer or market preferences as well as the cost of using these methods, which may not be easily passed on to the customer (Baker, 2016; Kecinski, Messer, Knapp, & Shirazi, 2017).…”
Section: Intervention Strategies For Eliminating V Parahaemolyticusmentioning
confidence: 99%